Quantification of classical HLA class I mRNA by allele‐specific, real‐time polymerase chain reaction for most Han individuals. (27th December 2017) - Pan, N.; Lu, S.; Wang, W.; Miao, F.; Sun, H.; Wu, S.; Nan, D.; Qiu, J.; Xu, J.; Zhang, J.
Abstract : Recent studies have shown that expression levels of different alleles at the same HLA class I locus can vary dramatically, which might have a broad influence on human disease. However, precise quantification of the relative expression level of each HLA allele is challenging, because distinguishing different alleles on the same locus is difficult. Here, we developed a series of allele‐specific, real‐time polymerase chain reaction assays for quantifying HLA class I allele mRNA in most Han individuals. The alleles of almost all heterozygous genotypes with a frequency higher than 0.5% in our population (78 alleles on HLA‐A locus, 124 alleles on HLA‐B locus, and 74 alleles on HLA‐C locus) were specifically amplified. The specificity of the amplification was strictly validated by setting the corresponding negative control for each allele of each genotype. The amplification efficiency of each reaction was determined, and the slopes of the reactions were compared. This study provides a tool for detecting the comprehensive expression profile of HLA class I alleles and will be useful not only for the investigation of the molecular mechanism underlying HLA allele expression regulation but also for exploration of immunological mechanisms involving HLA expression in the fields of tumour immune evasion, viral infection, auto‐immune disorders, and graft vs host disease after haematopoietic stem cell transplantation.